Octreotide ameliorates dermal fibrosis in bleomycin-induced scleroderma - Oyucu Orhan, Sibel; Tektemur, Ahmet; Gozel, Nevzat; Ozercan, Ibrahim Hanifi; Yolbas, Servet; Yildirim, Ahmet; Koca, Suleyman Serdar (Tubitak Scientific & Technological Research Council Turkey, 2018)
Background/aim: Insulin-like growth factor (IGF)-I is a differentiation and growth factor. Antifibrotic action of octreotide has been reported in pulmonary fibrosis. The present study aimed to research the prophylactic and therapeutic potential of octreotide on a bleomycin (BLM)-induced experimental scleroderma model. Materials and methods: Sixty Balb/c female mice were divided into 6 groups. Daily subcutaneous BLM (100 mu g) was injected for 3 weeks in groups II and III and for 6 weeks in groups V and VI. Octreotide (100 mu g/kg per day) was injected subcutaneously for the first 3 weeks in group III (prophylactic) and the second 3 weeks in group VI (therapeutic). Mice in groups I, II, and III were sacrificed at the end of the third week, while mice in groups IV, V, and VI were sacrificed at the end of the sixth week. Results: Repeated BLM applications increased dermal inflammatory cell counts and dermal thickness, and led to dermal fibrosis at both the third and sixth weeks. Moreover, mRNA expressions of TG F-beta 1 and IGF binding protein (IGFBP)-3 and -5 were higher in the BLM-injected sham groups. On the other hand, IGFBP-3 and -5 mRNA expressions were significantly decreased in both the prophylactic and therapeutic octreotide groups. Similarly, octreotide decreased dermal inflammatory infiltrations and dermal thickness. Conclusion: Octreotide has antifibrotic actions on experimentally induced dermal fibrosis. It can be suggested that IGF-I plays pathogenic roles, and octreotide is a candidate for research in the treatment of scleroderma.
Keywords: Scleroderma; dermal fibrosis; insulin-like growth factor-I; octreotide